Meningkatkan Kreativitas Dan Keterampilan Sosial Anak Berkebutuhan Khusus Perspektif Teori Neurosains Menurut Santiago Ramon Y Cajal - Umu Lailatussyarifah; Muhammad Zainudin; Alisa Kurniawati; Muhammad in’am Akmalilahya; Rahayu Sulistyawati; Tiara Safna Annida (PT. Nawa Edukasi Nusantara, 2025)
This journal examines the enhancement of creativity and social skills among children with special needs at SLB Marsudi Putra 1 Bantul through the lens of Santiago Ramón y Cajal's neuroscience theory. The study employs a qualitative case study approach, utilizing observation, interviews, and documentation to analyze the implementation of neuroplasticity in activities such as art, culinary arts, sewing, batik-making, and drumband. The research aims to identify neuroscience strategies for boosting creativity via new neural pathway formation and social skills through repeated interactions, while uncovering challenges like the need for repetitive learning among children with hearing impairments, intellectual disabilities, and autism. Findings indicate that individualized and routine approaches effectively strengthen brain synapses, aligning with the principle